PENGARUH INVESTASI, TENAGA KERJA, SERTA EKSPOR TERHADAP PERTUMBUHAN EKONOMI - Rendy Alvaro (Pusat Kajian Anggaran, 2021)
This study aims to determine the effect of foreign investment, domestic investment, labor, and exports on economic growth in Indonesia. This study uses panel data analysis consisting of cross sections and time series in provinces in Indonesia from 2012-2019. The results of the study indicate that foreign investment, domestic investment, and exports are found to have no effect on economic growth. Furthermore, the labor variable was found to have a significant negative effect on economic growth.